2016
DOI: 10.17511/ijpr.2016.i06.10
|View full text |Cite
|
Sign up to set email alerts
|

Clinical profile of childhood Guillain-Barre Syndrome

Abstract: Objective: Recognizing the clinical presentation of Guillain-Barre syndrome in children. Design: Retrospective observational study. Setting: Pediatric wards and Paediatric Intensive Care Unit. Method: A medical record files of 52 patients of GBS, between the periods of March 2011 to February 2016 were recovered from Medical Record and Statistics Section of institute. Files were analyzed for demographic data, clinical features, co-morbid conditions, investigations, electrophysiological data, mode and result of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
1
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 16 publications
(27 reference statements)
3
1
0
Order By: Relevance
“…Similar findings were noted by Meshram et al in their study. 18 Similar to other previous studies, in our study 93.3% of children had some antecedent symptoms with URTI (53.3%) being the most common. 11,12,15 Similar findings were noted in studies by Pijl et al and Kalita et al 19,20 However, in study by Rangan et al diarrhoea was the most prevalent antecedent illness.…”
Section: Discussionsupporting
confidence: 92%
“…Similar findings were noted by Meshram et al in their study. 18 Similar to other previous studies, in our study 93.3% of children had some antecedent symptoms with URTI (53.3%) being the most common. 11,12,15 Similar findings were noted in studies by Pijl et al and Kalita et al 19,20 However, in study by Rangan et al diarrhoea was the most prevalent antecedent illness.…”
Section: Discussionsupporting
confidence: 92%
“…1,4,6 Most commonly affected age group is 0-5 years which is consistent with studies done in Iran and against the other studies. 2,4 Most common symptom is motor in the form of ascending paralysis which is similar to other studies. 1,2,5,6,9 Antecedent illness is seen in 40% of cases among which URTI, is most common illness which is similar to other studies.…”
Section: Discussionsupporting
confidence: 86%
“…2,4 Most common symptom is motor in the form of ascending paralysis which is similar to other studies. 1,2,5,6,9 Antecedent illness is seen in 40% of cases among which URTI, is most common illness which is similar to other studies. 6 In outcome 73.3% children were discharged and mortality was 10% which is similar to other study done in Nagpur, few other studies showed mortality as high as 16.6% in New Delhi, as low as 6.6%in Mumbai.…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…6 In addition to respiratory failure, fatality in Guillain Barre Syndrome is due to serious disturbances in autonomic function. 7 Fluctuation in blood pressure, arrhythmias, bowel and bladder paralysis are cause of serious concern as these add in the morbidity associated with Guillain Barre Syndrome and quite often may be the cause of fatality. 7 This study was conducted to see the frequency and outcome of different autonomic disturbances in Guillain Barre Syndrome so that the need for proper monitoring and timely intervention may be improved.…”
Section: Introductionmentioning
confidence: 99%